BIODIVERSITY CONSERVATION AND ECOTOURISM IN URBAN FORESTS: A SYSTEMATIC REVIEW AND BIBLIOMETRIC ANALYSIS - Rhomi Ardiansyah; Stevie Vista Nissauqodry; Kaharuddin; Retno Nur Utami (BIOTROPIA, 2026)
HIGHLIGHTS- Urban forests link biodiversity protection with public health and recreation- Five key research themes reflect ecological, social, and behavioral insights- Visitor experiences influence support for conservation and green behaviors- Most studies focus on the Global North, leaving tropical cities underexplored- A new framework shows how cities can balance nature, tourism, and well-beingABSTRACTIn the era of urbanization, urban forests play a crucial role in connecting biodiversity conservation and human well-being, providing recreational and tourism benefits in urban areas. This study aims to analyze the intersection of urban forests, biodiversity conservation, and their interaction with visitors, including preferences, perceptions, and behavior. We examine 83 open-access articles published between 2010 and 2025, retrieved from Scopus databases, and analyzed using bibliometric mapping and keyword co-occurrence analysis with VOSviewer, including clustering and thematic trends. This review identified five research clusters, which are (1) urban ecosystem and biodiversity, (2) recreational and ecotourism, (3) visitor preference and well-being, (4) human-nature interaction, and (5) behavioral science and health. Our results show that interdisciplinary studies on urban forests have been conducted since 2020, with a focus on environmental services, mental health, psychology, and pro-environmental behavior. However, research remains geographically biased toward the Global North, with limited representation from tropical and developing cities despite their rich biodiversity and rapid urbanization. This study proposes a conceptual framework that integrates the ecological and social dimensions of urban forest research. It emphasizes the need for place-based, behaviorally informed, and interdisciplinary approaches to maximize the multifunctional benefits of urban forests. As cities grow, urban forests, which serve as areas where people encounter biodiversity in the city, can act as strategic platforms for biodiversity conservation, community engagement, and enhancing public awareness and perceptions of the environment.